Communication strategy of Wat Phra Sri Maha Uma Devi as a Hindu Tourism Destination in Bangkok - Boonplook, Kunyapas; Boonyanmetaporn, Wassida (Jurnal Kajian Komunikasi, 2024)
Background: Wat Phra Sri Maha Uma Devi, commonly known as Wat Khaek Silom, is a popular and important Hindu temple in Bangkok, serving as a tourist attraction. Through communication and promotion efforts through digital media and collaborating with various parties to create attractive religious tourism. Despite its popularity, research on effective communication strategies to increase its attractiveness as a religious tourism destination is limited. Purpose: This study aims to analyze and develop effective communication strategies to promote Wat Phra Sri Maha Uma Devi as a Hindu tourist destination in Bangkok. The focus of the research is on communication strategies that are carried out through integrating cultural and religious values, as well as utilizing the use of digital communication media. Methods: This research employed a qualitative approach using a case study methodology, including interviews and participatory observations of temple management, tourists, and the local community. This approach was taken to gain a thorough understanding of the experiences, views, and challenges in managing religious tourism. Results: The findings highlight that effective communication, such as the use of digital communication media platforms and multilingual educational materials, significantly enhances the tourist experience and promotes sustainable tourism. The challenges faced are maintaining the authenticity of the temples while meeting the growing demands of tourism. Conclusion: Wat Phra Sri Maha Uma Devi has successfully integrated religious and cultural elements with effective communication strategies, making it a major tourist destination for Hindus. Implications: The findings of this study provide insights for tourism authorities and temple management to develop sustainable communication strategies that balance cultural preservation with commercial development.